Decision support of facilities management practice in high rise buildings - Yahya, Mohamad Ridzuan; Abdul Rahim, Asiah; Ibrahim, Md Najib (2015)
It is vital to prioritize on developing facilities management (FM) decision support in operation and maintenance of high rise buildings in order to make sure building performance and building condition are excellent all the time. In Malaysia, there are various obstacles that FM is facing in managing all maintenance activities in high rise building. The research objectives are to identify the fundamental issue in FM for supporting technology of building systems in order to sustain sufficient economical and technical aspect in FM decision support and to analyze the relationship between human system and technology system of FM performance. Ten (10) high rise buildings were randomly selected in Klang Valley, Malaysia which interviewed building owners, in-house FM personnel, in-house building maintenance personnel, out-sourced consultants, out sourced contractors, tenants and end-users based on the economic and technical aspects of design and maintenance which are the quality, safety and service in FM. It is evident from the findings that FM decision support practice in Malaysia is still lacking of human system aspect due to the knowledge and quality of building design and maintenance such as workmanship, response time, down time, request for repairs, building audit as well as operational benchmarks improvement were not implemented consistently. In addition, operation and maintenance activities more concentrated on corrective maintenance rather than preventive maintenance. However, in technology system aspect, most high rise buildings is able to utilize advance building technology such as building automation system (BAS) in order to provide a better service. In conclusion, FM decision support practice in Malaysia is still far behind to reach an intelligent building system equipped with advance and sophisticated technologies.